2022
DOI: 10.3389/fendo.2022.867001
|View full text |Cite
|
Sign up to set email alerts
|

LGR4, a G Protein-Coupled Receptor With a Systemic Role: From Development to Metabolic Regulation

Abstract: Leucine-rich repeat-containing G protein-coupled receptor 4 (LGR4/GPR48), a member of the GPCR (G protein-coupled receptors) superfamily, subfamily B, is a common intestinal crypt stem cell marker. It binds R-spondins/Norrin as classical ligands and plays a crucial role in Wnt signaling potentiation. Interaction between LGR4 and R-spondins initiates many Wnt-driven developmental processes, e.g., kidney, eye, or reproductive tract formation, as well as intestinal crypt (Paneth) stem cell pool maintenance. Besid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“… 49 Several studies have highlighted the significant role of LGR4, a crucial Wnt/β-catenin regulator, in regulating BMSC differentiation as well as bone development and homeostasis. 19 , 50 Abnormal LGR4 expression was observed in a variety of bone loss diseases. 16 LGR4 -KO mice have been found to exhibit delayed osteogenic differentiation and mineralization.…”
Section: Discussionmentioning
confidence: 99%
“… 49 Several studies have highlighted the significant role of LGR4, a crucial Wnt/β-catenin regulator, in regulating BMSC differentiation as well as bone development and homeostasis. 19 , 50 Abnormal LGR4 expression was observed in a variety of bone loss diseases. 16 LGR4 -KO mice have been found to exhibit delayed osteogenic differentiation and mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…LGR4 also plays an important role in metabolic regulation, coordinating various metabolic signals. 21 Recently, Dong et al 22,23 described RSPO2/LGR4 as a key regulator for the differentiation of precursor cells into adipocytes. In addition, Li et al observed that the level of LGR4 in diabetes patients was significantly lower than that in non-diabetes patients (P<0.05), and the level of LGR4 in hypertensive patients was lower than that in non-hypertensive patients with higher blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…It also regulates OB differentiation in vivo and in vitro ( Luo et al, 2009 ). LGR4 is also present in different tissues and consequently it has been linked with systemic roles from development to metabolic regulation ( Filipowska et al, 2022 ).…”
Section: Bone Cellsmentioning
confidence: 99%
“…PTH appears to increase the amount of OB precursors in the bone marrow through a direct action. The bone marrow cells capable of differentiating to OBs are the colony-forming units-fibroblast (CFU-F) and old studies already demonstrated that the administration of PTH ( Kalantar-Zadeh et al, 2021 ; Csaba, 2022 ; Alberto Ortiz, 2022 ; Elshahat et al, 2020 ; Moe et al, 2006 ; Kidney Disease: Improving Global Outcomes KDIGO CKD-MBD Update Work Group, 2017 ; Wang et al, 2018 ; Kidney Disease: Improving Global Outcomes KDIGOCKD–MBD Work Group, 2009 ; Vervloet et al, 2014 ; Torregrosa et al, 2022 ; Llach et al, 2000 ; Lucas, 1883 ; Hruska et al, 2017 ; Goltzman et al, 2018 ; Day et al, 2005 ; Takada et al, 2007 ; Guo et al, 2010 ; Vasikaran et al, 2011 ; Tridimas et al, 2021 ; Bover et al, 2021a ; Bover et al, 2018 ; Bover et al, 2021b ; Wada et al, 2006 ; Gori et al, 2000 ; Luo et al, 2016 ; Luo et al, 2009 ; Filipowska et al, 2022 ; Luxenburg et al, 2007 ; Wheater et al, 2013 ; Rochefort et al, 2010 ; Orlando, 2020 ; Richter and Faul, 2018 ; Vervloet, 2020 ; Gutiérrez et al, 2008 ) to rats for 1 week resulted in the doubling of CFU-F compared with placebo-treated rats ( Nishida et al, 1994 ).…”
Section: Effects Of Parathyroid Hormone On Bone Tissuementioning
confidence: 99%